A Textual Analysis of the Use of Sunna in Malik's Legal Doctrine - Kusmana Kusmana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2000)
The sources of Malik's legal doctrine lie in texts, opinion and customary law. The textual sources of his doctrine consist of the paper will concentrate.